2021
DOI: 10.1016/j.ynpai.2021.100064
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of visceral pain and the role of the microbiome

Abstract: Visceral pain refers to pain arising from the internal organs and is distinctly different from the expression and mechanisms of somatic pain. Diseases and disorders with increased visceral pain are associated with significantly reduced quality of life and incur large financial costs due to medical visits and lost work productivity. In spite of the notable burden of illness associated with those disorders involving increased visceral pain, and some knowledge regarding etiology, few successful therapeutics have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“… 119 , 120 A recent review of the role of microbiome in animal models of visceral pain provides an excellent summary. 121 …”
Section: Affected Diseasesmentioning
confidence: 99%
“… 119 , 120 A recent review of the role of microbiome in animal models of visceral pain provides an excellent summary. 121 …”
Section: Affected Diseasesmentioning
confidence: 99%
“…Multiple animal models of VH were used to explore these mechanisms. Some studies reported that repeated CRD in rat neonates induces VH in adulthood [ 29 , 30 ]. Lee et al examined rats with water avoidance stress-induced colonic hypersensitivity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Taking this into account, numerous animal models have been developed for the assessment of visceral sensitivity in normal conditions or in states of sensitization. A systematic review of these models is out of the scope of the present work and can be found [8][9][10][11] Several animal models of intestinal hypersensitivity have been developed based on the evidence that inflammation seems to be a pathophysiological component of inflammatory and functional GI disorders, as mentioned above. Overall, postinflammatory models have been based on the local administration (intracolonic enemas) of different active compounds (such as acetic acid, capsaicin, mustard oil, zymosan, trinitrobenzene sulfonic acid (TNBS)-or dinitrobenzene sulfonic acid (DNBS)) [12][13][14][15][16] or the experimental infection with biological agents (such as Trichinella spiralis, Nippostrongylus brasiliensis or Campylobacter species).…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account, numerous animal models have been developed for the assessment of visceral sensitivity in normal conditions or in states of sensitization. A systematic review of these models is out of the scope of the present work and can be found elsewhere [see as examples: Regmi and Shah (2020); Johnson et al (2020); West and McVey Neufeld (2021); Accarie and Vanuytsel (2020)] 8–11 . Several animal models of intestinal hypersensitivity have been developed based on the evidence that inflammation seems to be a pathophysiological component of inflammatory and functional GI disorders, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%